Innovations in Practice: Using clinician‐rated outcomes to support improved service decision making in a Child and Adolescent Mental Health Service. Issue 1 (10th December 2016) - Fuggle, Peter; Cleridou, Kalia
Abstract : Background: Clinical outcomes are now routinely collected in most services. However, there is a need to make full use of the information collected in order to improve the use of limited Child and Adolescent Mental Health Service (CAMHS) resources. This paper describes a method of improving service decision making by making the interpretation of outcomes data accessible to frontline staff. Method: Clinician ratings of child outcomes for 2876 cases were routinely collected between 2009 and 2013 in a single CAMHS service. These outcomes were assessed against seven 'point of entry' and 'treatment' variables. Results: Older children, referred by social care and presenting with multiple problems were associated with worse treatment outcomes than other service users. These findings were used to create an accessible Service Evaluation Chart of outcomes, to support discussion and decision making within the service. This process enabled the identification of a group who had particularly poor outcomes and resulted in consideration about service changes to try to improve outcomes for this specific group. Conclusions: Providing clinicians with accessible information about outcomes promotes the likelihood of outcomes being used in service decision making.